1993
DOI: 10.1002/bem.2250140104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 60 Hz magnetic field on central cholinergic systems of the rat

Abstract: We studied the effects of an acute (45 min) exposure to a 60 Hz magnetic field on sodium-dependent, high-affinity choline uptake in the brain of the rat. Decreases in uptake were observed in the frontal cortex and hippocampus after the animals were exposed to a magnetic field at flux densities > or = 0.75 mT. These effects of the magnetic field were blocked by pretreating the animals with the narcotic antagonist naltrexone, but not by the peripheral opioid antagonist, naloxone methiodide. These data indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 50 publications
2
34
1
Order By: Relevance
“…An MF can noninvasively create electric fields in deep underlying structures, thereby modulating oxidative stress, apoptosis, release of neurotransmitters, secretion of neurotrophic factors, and axonal growth. [26][27][28][29][30][31] In rat models of spinal cord injury (SCI), exposure to a low intensity MF results in significant improvement in locomotor, sensorimotor, and autonomic function. [32][33][34][35][36] Stimulation of the motor cortex by repetitive transcranial magnetic stimulation is beneficial, especially in lower thoracic SCI lesions, because it activates the central pattern generator via descending serotonin pathways.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An MF can noninvasively create electric fields in deep underlying structures, thereby modulating oxidative stress, apoptosis, release of neurotransmitters, secretion of neurotrophic factors, and axonal growth. [26][27][28][29][30][31] In rat models of spinal cord injury (SCI), exposure to a low intensity MF results in significant improvement in locomotor, sensorimotor, and autonomic function. [32][33][34][35][36] Stimulation of the motor cortex by repetitive transcranial magnetic stimulation is beneficial, especially in lower thoracic SCI lesions, because it activates the central pattern generator via descending serotonin pathways.…”
Section: Introductionmentioning
confidence: 99%
“…These results are comparable with previous reports of repeated low-intensity MF stimulation in SCI rats and may be mediated by the effects of the MF on free radical-induced secondary injury or by activation of the central pattern generator center for locomotion by serotonin pathways. [28][29][30][31][32][33][34][35][36] 5-Hydroxytryptamine has an important role in modulating the excitability of motor and sensory neurons in the spinal cord, thereby influencing locomotion and sensorimotor behavior. [51][52][53][54][55] Exposure to an MF has been shown to restore the metabolism, synthesis, and distribution of 5-hydroxytryptamine in the spinal cord and brain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies have demonstrated that acute in vivo exposure to a high-intensity (0.14 T) static magnetic field (Kristofikova et al 2005) and to 60 MHz magnetic fields (Lai et al 1993;Lai & Carino 1999) decrease cholinergic activity in the rat hippocampus. This magnetic field-induced diminution in sodium-dependent high-affinity choline uptake caused performance deficits in a radial-arm maze (Lai 1996).…”
Section: Discussionmentioning
confidence: 88%
“…ELF-MF is MF with a range of frequency of 3 to 30Hz. Even so, MF has been shown to affect proliferation and growth factor expression in cultured cells [9]- [11] and also interfere with endorphinergic and cholinergic system [12]- [14]. Other than MF, electrical fields (EF) also have biological effects that can influence neural growth and orientation in vitro [15], and have been applied for the treatment of spinal cord injuries in recent clinical trials [16].…”
Section: Introductionmentioning
confidence: 99%